The use of modified TI-RADS using contrast-enhanced ultrasound features for classification purposes in the differential diagnosis of benign and malignant thyroid nodules: A prospective and multi-center study - Zhou, Ping; Chen, Feng; Zhou, Peng; Xu, Lifeng; Wang, Lei; Wang, Zhiyuan; Yu, Yi; Liu, Xueling; Wang, Bin; Yan, Wei; Zhou, Heng; Tao, Yichao; et al. (Frontiers in Endocrinology, 2023)
Objectives: To evaluate the diagnostic efficacy of a modified thyroid imaging reporting and data system (TI-RADS) in combination with contrast-enhanced ultrasound (CEUS) for differentiating between benign and malignant thyroid nodules and to assess inter-observer concordance between different observers. Methods: This study included 3353 patients who underwent thyroid ultrasound (US) and CEUS in ten multi-centers between September 2018 and March 2020. Based on a modified TI-RADS classification using the CEUS enhancement pattern of thyroid lesions, ten radiologists analyzed all US and CEUS examinations independently and assigned a TI-RADS category to each thyroid nodule. Pathology was the reference standard for determining the diagnostic performance (accuracy (ACC), sensitivity (SEN), specificity (SPN), positive predictive value (PPV), and negative predictive value (NPV)) of the modified TI-RADS for predicting malignant thyroid nodules. The risk of malignancy was stratified for each TI-RADS category-based on the total number of benign and malignant lesions in that category. ROC curve was used to determine the cut-off value and the area under the curve (AUC). Cohen's Kappa statistic was applied to assess the inter-observer agreement of each sonological feature and TI-RADS category for thyroid nodules. Results: The calculated malignancy risk in the modified TI-RADS categories 5, 4b, 4a, 3 and 2 nodules was 95.4%, 86.0%, 12.0%, 4.1% and 0%, respectively. The malignancy risk for the five categories was in agreement with the suggested malignancy risk. The ROC curve showed that the AUC under the ROC curve was 0.936, and the cutoff value of the modified TI-RADS classification was >TI-RADS 4a, whose SEN, ACC, PPV, NPV and SPN were 93.6%, 91.9%, 90.4%, 93.7% and 88.5% respectively. The Kappa value for taller than wide, microcalcification, marked hypoechoic, solid composition, irregular margins and enhancement pattern of CEUS was 0.94, 0.93, 0.75, 0.89, 0.86 and 0.81, respectively. There was also good agreement between the observers with regards to the modified TI-RADS classification, the Kappa value was 0.80. Conclusions: The actual risk of malignancy according to the modified TI-RADS concurred with the suggested risk of malignancy. Inter-observer agreement for the modified TI-RADS category was good, thus suggesting that this classification was very suitable for clinical application.